Mejoramiento genetico de la habichuela en el CIAT y resultados de viveros internacionales - Montes de Oca B., Gustavo (International Center for Tropical Agriculture, 1987)
Aspects of snap bean genetic improvement at CIAT are briefly analyzed. They include plant cycle and yield, strategies and methods for improvement, segregating population management, and description of characters to be evaluated. Data on the climbing and bush germplasm selected for the germplasm bank are included as well as on BGMV-resistant cv., snap bean climbing and bush lines selected for regional trials, and national and international germplasm deliveries carried out in 1986-87 and 1987, resp. (CIAT)